Abstract 027: Adjunctive Intra‐Arterial Tenecteplase Following Mechanical Thrombectomy. (ALLY) Pilot Trial - Hisham Alhajala; Alicia Castonguay; Mouhammad Jumaa; Rahul Rao; Sunil Sheth; Marion Oliver; Richard Burgess; Ashutosh Jadhav; Diogo Haussen; Osama O Zaidat; Syed Fazal Zaidi (Stroke: Vascular and Interventional Neurology)
Introduction Intraarterial thrombolytic treatment after mechanical thrombectomy (MT) in patients with large vessel occlusion ischemic stroke may improve the odds of achieving complete reperfusion and favorable functional outcome at 90 days. This study evaluated the safety and efficacy of intraarterial Tenecteplase (IA TNK) as an adjunctive therapy to mechanical thrombectomy in patients with anterior circulation large vessel occlusion. The primary safety endpoint is the rate of symptomatic ICH within 24 hours of treatment with IA TNK. The primary efficacy endpoint is the proportion of patients with improvement of reperfusion. The secondary endpoints included final revascularization grade, discharge mortality, and any intracranial hemorrhage. Methods ALLY is a prospective, single‐center, single‐arm pilot study (ClinicalTrials.gov Identifier: NCT05172934). The study enrolled adult patients ≥18 and ≤85 years with large vessel (ICA or MCA) occlusion, with pre‐morbid mRS ≤3 who underwent mechanical thrombectomy and achieved incomplete reperfusion with a final TICI score of 2b and 2C. All enrolled subjects received at least one dose of 1.5 mg IA TNK. Additional treatments were administered at the discretion of the operator to a maximum of 4.5 mg IA TNK. Treatments were administered as a bolus in 3 divided doses given 5 minutes apart, with angiographic runs obtained before and after the final treatment. All patients had imaging follow up (MRI of CT) after 24 hours of treatment. Clinical assessment was completed with NIHSS and mRS scales. Angiographic and imaging data were adjudicated by an independent core laboratory. Results ALLY is a prospective, single‐center, single‐arm pilot study (ClinicalTrials.gov Identifier: NCT05172934). The study enrolled adult patients ≥18 and ≤85 years with large vessel (ICA or MCA) occlusion, with pre‐morbid mRS ≤3 who underwent mechanical thrombectomy and achieved incomplete reperfusion with a final TICI score of 2b and 2C. All enrolled subjects received at least one dose of 1.5 mg IA TNK. Additional treatments were administered at the discretion of the operator to a maximum of 4.5 mg IA TNK. Treatments were administered as a bolus in 3 divided doses given 5 minutes apart, with angiographic runs obtained before and after the final treatment. All patients had imaging follow up (MRI of CT) after 24 hours of treatment. Clinical assessment was completed with NIHSS and mRS scales. Angiographic and imaging data were adjudicated by an independent core laboratory. Conclusion Ally pilot study demonstrated that adjunctive intraarterial Tenecteplase to mechanical thrombectomy was safe and feasible without major complications. Although there was no change in final reperfusion TICI score, there was evidence of improved distal perfusion on angiographic images.